microRNA-33A expression is reduced in cerebral cortex in a rat model of ischemic tolerance - Feng, Y; Li, W; Wang, J Q (Cellular and Molecular Biology, 2015)
This study examined the microRNA-33a (miR-33a) expression levels in cerebral cortex in rat model of cerebral ischemic tolerance (IT), with 3-nitropropionic acid (3-NPA) preconditioning. Rat model of cerebral IT was established as follows: 14 male Sprague-Dawley rats were randomly divided into two groups, the 3-NPA treated group and the control group. Intraperitoneal injection of 3-NPA or normal saline was performed in 3-NPA treated group and control group, respectively. Middle cerebral artery occlusion (MCAO) was performed in all the rats 3 days after injection and the infarct volume was measured on postoperative day-2. To study miR-33a expression levels in this model, male Sprague-Dawley rats (n = 31) were randomly divided into 4 groups, 3-NPA treatment group (n = 8), 3-NPA treatment + MCAO group (n = 9), MCAO group (n = 9), and control group (n = 5). Surviving rats were sacrificed 4 days after injection and cerebral cortex samples were obtained for total RNA isolation. MiR-33a expression levels were determined by real-time quantitative PCR (qRT-PCR). Infarct volume in 3-NPA treated group decreased significantly in comparison to the control group (P < 0.05). Expression analysis by qRT-PCR revealed that miR-33a expression levels in 3-NPA treated group were significantly higher than that in control group (P < 0.05). However, no statistically significant difference in miR-33a expression levels were observed in 3-NPA + MCAO and MCAO groups (both P > 0.05). Our results present convincing evidence that miR-33a expression levels are significantly reduced in the cerebral cortex in rat model of cerebral IT, which may have significantly impacted the infarct volume.